Climate Change for Community and National Development: Challenges and Opportunities in the 21st Century - Adeosun, Motunrayo Ajoke; Oladapo, Olubunmi Cecilia; Ojo, Ronke Christiana (Interdisciplinary Journal Of Lifelong Learning, 2025)
In Nigeria, climate change intensifies social and environmental stress and exacerbates entrenched gender inequalities. Extreme weather (floods, droughts) and resource scarcity disrupt schooling and livelihoods, undermining education access for girls. For example, recent floods destroyed farmland and displaced thousands, worsening food insecurity and limiting household coping capacity. These, crises increase women’s burdens – longer treks to fetch water and fuel and heightened health risks (waterborne disease, heat stress) – and elevate risks of gender-based exploitation during displacement. As a result, gender gaps widen literacy among young women is 90% in the south but under 30% in many northern states (such as Sokoto, Bauchi, Zamfara). The study highlights broad implications: Climate pressures damage school infrastructure and hinder attendance, while related malnutrition and health issues impede learning outcomes. Women’s economic participation suffers as climate impacts agriculture and livelihoods. In Nigeria, women often farm marginal land, so climate shocks disproportionately reduce yields and incomes. Gender and asset gaps limit adaptive capacity; closing these gaps through empowerment and inclusion is vital. The authors conclude that inclusive, climate-responsive educational reforms and gender-focused development strategies are essential. Prioritizing girls’ education and women’s empowerment can bridge Nigeria’s regional disparities and drive resilient national development. Education and empowerment emerge as key solutions: stakeholders stress that educating girls builds climate awareness and innovation, forming the ‘’foundation of women empowerment to ensure sustainable development’’. Empowerment programmes such as financial services, training, climate-smart agriculture bolster resilience and adaptive capacity.